A Novel Self-Powered Wireless Sensor Node Based on Energy Harvesting for Mechanical Vibration Monitoring. (30th March 2014) - Zhang, Xihai; Fang, Junlong; Meng, Fanfeng; Wei, Xiaoli
Abstract : Wireless sensor networks (WSNs) have been expected to improve the capability of capturing mechanical vibration dynamic behaviors and evaluating the current health status of equipment. While the expectation for mechanical vibration monitoring using WSNs has been high, one of the key limitations is the limited lifetime of batteries for sensor node. The energy harvesting technologies have been recently proposed. One of them shares the same main idea, that is, energy harvesting from ambient vibration can be converted into electric power. Employing the vibration energy harvesting, a novel self-powered wireless sensor node has been developed to measure mechanical vibration in this paper. The overall architecture of node is proposed. The wireless sensor node is described into four main components: the energy harvesting unit, the microprocessor unit, the radio transceiver unit, and accelerometer. Moreover, the software used to control the operation of wireless node is also suggested. At last, in order to achieve continuous self-powered for nodes, two operation modes including the charging mode and discharging mode are proposed. This design can effectively solve the problem of continuous supply power of sensor node for mechanical vibration monitoring.